PLASMA INSULIN AND IGF-1 AND HEPATIC ACTIVITY IN SAANEN GOAT KIDS, AROUND WEANING - Damiano Magistrelli (Tropical and Subtropical Agroecosystems, 2009)
Weaning is a crucial event in the life of young ruminants. At weaning ruminal and digestive activity are still incomplete, so weaning may coincide with a period of growth stasis. Since insulin and insulin-like growth factor 1 (IGF-1) can play a fundamental role in post-natal development, the aim of the present study was to evaluate plasma variations of insulin and IGF-1 levels and their relationships with the hepatic activity, around weaning. For this purpose, eleven 3-days-old Saanen goat kids were randomly divided into MILK (6 animals) and WMIX (5 animals) groups. All kids were fed goat milk to age 29 days. After that, MILK kids continued to receive milk, while WMIX ones underwent weaning, based on the progressive replacement of milk with solid feed. WMIX kids were completely weaned on day 48. Blood samples were weekly analyzed for metabolic traits, insulin and IGF-1 levels, alanine aminotransferase (ALT) and aspartate aminotransferase (AST) activities. On day 50, all animals were slaughtered, liver weight was recorded and liver samples were analyzed for DNA, RNA, phospholipids, glicogen and soluble protein content, ALT and AST activity. On day 50, plasma insulin and IGF-1 were lower in WMIX group, as possible consequence of the lower plasma glucose and amino acids levels. Liver weight was not different between groups, but liver weight expressed as percentage of body weight was lower in WMIX kids and highly correlated to plasma IGF-1. Liver glycogen was also lower in WMIX kids, as possible consequence of the lower plasma glucose. Hepatic ALT and AST activities were not different between groups and both were strongly correlated to plasma insulin. Moreover, insulin was positively correlated to the proteosynthetic capability per cell (RNA/DNA) of the liver. Our results indicate that the adopted livestock practice permitted the normal development of the animal used, avoiding growth stasis. Anyway, weaning altered plasma insulin and IGF-1, without affecting neither hepatic activity of aminotransferases, nor hepatic DNA and RNA content. Interestingly, plasma insulin was positively correlated to hepatic ALT and AST activity and proteosynthetic capability per cell, suggesting a role for insulin as indicator of hepatic aminotransferase and proteosynthetic activity.